United States. Army. 5th Infantry Regiment records - United States. Army. Infantry Regiment, 5th (1815- )
Description and illustration of the coat of arms of the regiment.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Army -- Heraldry